Vibration analysis of double elastomer layered superstructures with extended locally continuous support model - Ulu, Arif; Metin, Muzaffer; Arikoglu, Aytac (TAYLOR & FRANCIS INC, 2024)
In this study, a distributed rail pad (RP) model of rail supported by double elastomer layers for rigid superstructures like light metro is presented, and a semi-analytical solution is derived via the Galerkin's method. Apart from existing distributed RP models that contain multiple individual spring-dampers, the proposed method offers locally continuous rail bedding. The new model assumes that the rail bedding is not pointwise and connects the continuous bedding and lumped baseplate mass with a derived function, which is the first novelty of the paper. Results of the single-spring model (SSM) and extended locally continuous support models (ELCSM) are obtained and compared to indoor and outdoor measurements in the time and frequency domains. The proposed model shows similar results to the conventional model for dynamic response; however, the clear difference between the models is seen at high resonant frequencies because of the stiffer bedding of the rail. Another point is that rail stresses and displacements can be calculated more accurately compared to SSM, due to including the length of RP. The findings of the study highlight the importance of considering RP length and stiffness when designing and maintaining railway tracks and provide insights into how to optimize these parameters for better performance and durability.
Keywords: Railway; Timoshenko beam theory; Galerkin method; extended locally continuous support; distributed rail pad; TRAIN-TRACK SYSTEM; DYNAMIC-RESPONSE; RAILWAY TRACK; SLAB TRACK; VEHICLE; CORRUGATION; BEHAVIOR; Mechanics